MANIPULATIVE ELECTORAL TECHNOLOGIES AS AN INSTRUMENT OF DISTORTION IN THE IMPLEMENTATION OF REGIONAL POLICY - Dubel, Mykhaylo (Public Management and Policy, 2026)
The purpose of this study is to determine the specific features of the use of manipulative electoral technologies as a distorted instrument for the implementation of state regional policy. The relevance of the study is due to the fact that the phenomenon of gerrymandering is inherent in both stable, highly developed democratic states, such as the United States and the United Kingdom, and in developing ones. The selection of Malaysia and Ethiopia as case studies was determined by a combination of several factors, including their federal structure and the significant influence of ethnic minority factors within particular regions. The experience of Malaysia demonstrates that the combination of the first-past-the-post electoral system, ethnically structured electoral behavior, and the broad discretion of the Election Commission in the process of redistricting created favorable conditions for the development of both malapportionment and partisan as well as ethnic gerrymandering. Consecutive constitutional amendments effectively weakened restrictions concerning the equality of constituencies and provided the authorities with opportunities to influence the configuration of electoral maps in accordance with their own political interests. As a result, the electoral system, which formally was intended to ensure governmental stability and political competitiveness, for a long time contributed to preserving the dominance of the ruling coalition. At the same time, the example of the state of Johor demonstrates that the ethnic composition of the population and the territorial concentration of particular groups may become key instruments of electoral manipulation. No less illustrative is the example of the Harari Region in Ethiopia, where gerrymandering acquires a specific form by being combined with seat reservation mechanisms and special voting rights for ethnic minorities. On the one hand, such a model contributes to ensuring the political representation of the Harari people and creates mechanisms for protecting their right to self-determination. On the other hand, the excessive disproportionality between constituencies, the inequality of electoral power, and the actual dominance of particular ethno-political groups indicate a serious violation of the principle of equal suffrage. In this context, gerrymandering functions not only as an instrument of political representation, but also as a mechanism for consolidating ethnic politics and restricting political competition.